Identifikasi Bahaya dan Penilaian Risiko K3 pada Industri Rumah Tangga Tempe XYZ menggunakan Metode HIRADC di Desa Kaloran, Nganjuk - Ilham Sandya Putra; Sekar Ayu Wulandari; Septine Brillyantina; Rahmat Dhandy (Studia : Journal of Humanities and Education Studies, 2026)
Home Industry Tempe XYZ in Kaloran Village, Nganjuk, faces various Occupational Health and Safety (OHS) hazards due to traditional technology utilization, wet work environments, and the absence of a documented OHS system, leading to workplace accidents and health complaints among workers. This study aims to identify potential hazards, assess OHS Risk Levels, and formulate risk control recommendations based on the hierarchy of controls across all stages of tempeh production. This descriptive qualitative research with a case study design applies the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. Data were gathered through direct observation, semi-structured interviews with the total worker population of 4 people, documentation, and technical triangulation, with risk assessment conducted using a 5x5 semi-quantitative matrix. The study identified 30 potential hazards across 10 production steps, categorized into 3 very high-risk hazards (boiling water splashes during the first and second boiling processes, and electrical installations near wet areas), 3 high-risk hazards (exposure to hot steam and contact with rotating machine parts), 20 medium-risk hazards (slippery floors, manual material handling, and awkward bending postures), and 4 low-risk hazards. In conclusion, the boiling and milling steps pose the highest OHS risks. Control priorities are directed toward engineering controls such as machine guards, boiling pot covers, and drainage improvements, followed by administrative controls through Standard Operating Procedures (SOP) and consistent use of personal protective equipment.